Model of superior semicircular canal dehiscence: asymmetrical vestibular dysfunction induces reversible balance impairment - Hong, Sean S.; Wackym, P. Ashley; Murphy, Damian J.; Peci, Eran; Kiel, Matthew Y.; Tucker, Aaron; Carayannopoulos, Nicolas L.; Chandrasekar, Shrivaishnavi C.; Suresh, Nikhil; Utku, Umut A.; Yao, Justin D.; Mowery, Todd M. (Frontiers in Neurology, 2024)
Background: Superior semicircular canal dehiscence (SSCD) is a vestibular-cochlear disorder in humans in which a pathological third mobile window of the otic capsule creates changes to the flow of sound pressure energy through the perilymph/endolymph. The primary symptoms include sound-induced dizziness/vertigo, inner ear conductive hearing loss, autophony, headaches, and visual problems. We have developed an animal model of this human condition in the Mongolian Gerbil that uses surgically created SSCD to induce the condition. A feature that is unique in this model is that spontaneous resurfacing of the dehiscence occurs via osteoneogenesis without a subsequent intervention. In this study, we completed our assessment of this model to include reversible asymmetrical vestibular impairments that interfere with balance. Methods: Adult Mongolian gerbils (N = 12) were trained to complete a balance beam task. They were also trained to perform a Rotarod task. After 10 days of training, preoperative ABR and c+VEMP testing was followed by a surgical fenestration of the left superior semicircular canal. Balance beam testing recommenced at postoperative day 6 and continued through postoperative day 15 at which point final ABR and c+VEMP testing was carried out. Results: Behavioral comparison of preoperative and postoperative performance show a significant decrease in Rotarod performance, increased rates of falling, and an increase in time to cross the balance beam. Impairments were the most significant at postoperative day 7 with a return towards preoperative performance by postoperative day 14. This behavioral impairment was correlated with residual impairments to auditory thresholds and vestibular myogenic amplitudes at postoperative day 14. Conclusion: These results confirm that aberrant asymmetric vestibular output in our model of SSCD results in reversible balance impairments. The level of these behavioral impairments is directly correlated with severity of the vestibular dysfunction as we have previously reported for peripheral ear physiology and cognition.